2019
DOI: 10.1016/j.neuroimage.2019.116118
|View full text |Cite
|
Sign up to set email alerts
|

Sensory processing and categorization in cortical and deep neural networks

Abstract: Many recent advances in artificial intelligence (AI) are rooted in visual neuroscience. However, ideas from more complicated paradigms like decision-making are less used. Although automated decision-making systems are ubiquitous (driverless cars, pilot support systems, medical diagnosis algorithms etc.), achieving human-level performance in decision making tasks is still a challenge. At the same time, these tasks that are hard for AI are easy for humans. Thus, understanding human brain dynamics during these de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…is called transfer function and predicts average firing rate, similar to activation functions in deep neural networks 59,60 . Also, X  is the rate-constant of postsynaptic filtering, δ is synaptic gain and η is the postsynaptic potential at which the half of the maximum firing rate is achieved, see e.g.…”
Section: Deep Neural Fields Describe Neural Ensemble Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…is called transfer function and predicts average firing rate, similar to activation functions in deep neural networks 59,60 . Also, X  is the rate-constant of postsynaptic filtering, δ is synaptic gain and η is the postsynaptic potential at which the half of the maximum firing rate is achieved, see e.g.…”
Section: Deep Neural Fields Describe Neural Ensemble Activitymentioning
confidence: 99%
“…In turn, correlation distances between DMs, known as deviations, express second order differences, that is, differences in pairwise differences in neural activity or electric fields in different brain areas for the same cued locations. We used deviations to test for significant correspondence between memory representations 60,87,88 .   and 300 degrees) hemifield form distinct clusters, shown by ellipses.…”
Section: The Same Memory Is Stored By Electric Fields In Different Br...mentioning
confidence: 99%
“…This paper follows upon our recent work that focused on groups of neurons that represent memories known as neural ensembles (Figure 1). In 60 we studied computations performed by neural ensembles during a flexible sensorimotor decision making task 61 . We showed that neural ensembles in the same brain area performed different computations based on the rule applied during each trial, although the stimulus processed was the same.…”
Section: Deep Neural Fields Describe Neural Ensemble Structure In a Holistic Fashionmentioning
confidence: 99%
“…This paper and 29 focus on the structure and biophysics of neural ensembles. In related work 60 , we also studied the computations performed by ensembles using deep neural networks and behavioural models.…”
Section: Deep Neural Fields Describe Neural Ensemble Structure In a Holistic Fashionmentioning
confidence: 99%
“…Some theoretical models have been proposed to explain how the category is learned in the neural system ( 26 28 ). But most of models show categorical phenomena that are consistent with some behavioral results, without showing neural activity that encodes category information observed in the PFC or other brain areas ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%